An improved methodology for quantifying the impact of human activities on hydrological drought change - Junju Zhou; Qiaoqiao Li; Aizhong Ye; Shizhen Xu; Yunhan Yuan; Shiqin Xu; Dongxia Zhang; Xi Zhao; Yanbing Zhu; Yaru Zhao; Dongxiang Xue; Jiao Dou; et al. (Journal of Hydrology: Regional Studies, 2023)
Study region: Upper Shiyang River in the eastern Qilian Mountains, China. Study focus: Quantifying the impacts of anthropogenic and climate change on wet and dry hydrological variability was done by improving the Slope Change Ratio of Cumulative Quantities (ISCRCQ) method. New hydrological insights for the region: The scientific method is critical to quantify the driving factors of dry-wet hydrological changes. In this study, the slope change ratio of cumulative quantity (SCRCQ) method was improved to quantify the impacts of human activities and climate change on dry-wet hydrological changes. The results show a hydrological aridification trend at an annual scale from 1961 to 2016 in the upper reaches of the Shiyang River. However, the dry-wet hydrological change trends of the six tributaries differed: the hydrological humidification of the four western tributaries was apparent, while the remaining tributaries showed hydrological aridification. The influences of human activities and climate change on dry-wet hydrological changes were also evidently distinct in the different tributaries. Changing in climate is a vital factor triggering the dry-wet hydrological changes in the western tributaries, while human activities have completely changed the direction of the dry-wet hydrological changes and intensified the hydrological aridification in the eastern tributaries. Human activities have resulted in an increase both in the frequency of droughts and in the risk of socio-economic droughts. Thus, human activities in the region of eastern tributaries should be controlled within reasonable limits.